Lykke-Per i Tyskland: – fra berømt til glemt? - Hastenplug, Marlene (Pontoppidaniana, 2025)
Abstract The article examines the publication and reception history of Henrik Pontoppidan’s novel Lykke-Per in the German-speaking world. First published in 1906 as Hans im Glück, translated by Mathilde Mann and issued by Insel Verlag, the novel received praise from intellectuals such as Ernst Bloch, Georg Lukács, and Thomas Mann. Insel’s director Anton Kippenberg and his wife Katharina considered the novel a masterpiece – but commercial success proved elusive. The article draws on archival correspondence between Pontoppidan, Mann, and Insel, highlighting key obstacles to the novel’s distribution: its two-volume format, low market interst in Nordic literature, and Pontoppidan’s tendency to keep reworking what was already published. The paper shortages of the First World War further weakened its reach. Subsequent editions of Hans im Glück, including a revised East German edition in the 1970s and a paperback edition in West Germany in the 1980s, likewise failed to attract a wide readership. The article ultimately argues that while Lykke-Per had influential admirers in Germany, its actual readership remained limited, and Pontoppidan never achieved the renown there enjoyed by some of his Danish peers.